Preparation of graphene oxide (GO)/lanthanum coordination polymers for enhancement of bactericidal activity - Wang, Jia; Shan, Zezhi; Tan, Xiao; Li, Xinxiang; Jiang, Zhenqi; Qin, Jieling (Journal of materials chemistry. B, Materials for biology and medicine, 2021)
In this study, graphene oxide/lanthanum coordination polymer (GLCP) nanocomposites are prepared and their bactericidal activities against seven typical Pathogenic bacteria are evaluated. The GLCPs are fabricated through the electrostatic self-assembly of La ions on negatively charged graphene oxide (GO), followed by the stabilization of π-π stacking to ensure the formation of lanthanum coordination polymers on the GO surface. The morphologies and structures of the synthesized GLCPs are characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), ultraviolet-visible (UV-vis) spectroscopy, Fourier transform infrared (FT-IR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA). Moreover, the bactericidal effects of the well-coordinated GLCPs are investigated using the zone of inhibition and flat colony counting methods, as well as by determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The five GLCPs synthesized in this study exhibit broad-spectrum antibacterial activities against seven typical Pathogenic bacteria . We believe that our study could serve as a starting point to prepare bactericidal materials for further applications. The synthesized GO/lanthanum coordination polymers exhibit broad-spectrum antibacterial activities against seven typical Pathogenic bacteria , are compatible with large-scale preparation and can be harnessed as antibacterial compounds.